Luta por direitos, memória e repressão no alvorecer da ditadura civil-militar : o caso do sindicalismo rural na cidade de Andirá/PR - Alvares, Angélica Ramos (2017)
The current dissertation aims to examine the fight for social rights of the rural workers at the threshold of the civil-military dictatorship. In order to achieve so, we are going to take the path of the leaderships of the syndical movement of the farm workers of Andirá, a city in the north of state of Paraná, as case study. In order to support our object we are going to use as source the Military Police Inquiry (MPI), number 384/ Brasil Nunca Mais number 238 (Brazil No More nº 238), established on May 29th, 1964, in Andirá City as well as the biographical reports of Edmundo Bonesso, one of the main leaders of the União dos Lavradores e Trabalhadores em Geral de Andirá /PR (ULTGA) [Farmers and Rural Workers in General of Andirá City Union]. At the pre-1964 background, the rural syndicates and unions/associations set themselves as spokesperson of the proletarians on what concerns their claiming struggles. Immediately afterwards the military coup those organizations were the first ones to fall into the hands of the repression crafted by civil-military dictatorship. Through the MPI/judicial process we manage to pinpoint that the procedures and actions taken by the syndicalist during the civil-military dictatorship, especially in its the early years, were received by the military as ?subversion?. On the other hand, following the biographical reports from Edmundo Bonesso, the very same facts are seen as an authentic fight for rights. Thus, we walk on a land on which both sides engage in a constant duel for ?truth?, a truth designed in synch with the political struggle in progress in Brazil in April of 1964